إدارة الكفاءات ودورىا في تنمية السلوك الإبداعي دراسة ميدانية بالمديرية العملية لاتاالات الزاارر بالزلفة: Competency management and its role in developing creative behavior, a field study at the Operational Directorate of Algeria Telecom in Djelfa. - الحمداني نوري محمد; هزرشي طارق; سبع عارشة (Journal of North African Economies, 2025)
The study aimed to identify the role of competency management in developing the creative behavior of workers, at the Operational Directorate of Algeria Telecom.in Djelfa, and in order to achieve this goal, a questionnaire was designed that included (32) items to collect all the information, as it was distributed randomly to a sample of (40) individuals. Out of (50), data were collected and analyzed and hypotheses were tested using the (Spss) program, and the results of the study showed through the statistical results the average level of both competency management and creative behavior from the employees’ point of view, and it was also found that there is a statistically significant effect. At the level of (α≤ 0.05) for the Compensation for competencies on the development of creative behavior, and one of the most important recommendations of the study is the necessity to intensify the efforts of the Operational Directorate of Algeria Telecom. in Djelfa in the field of developing its human competencies with providing an appropriate environment that supports creativity and innovation.